The role of personal innovativeness in influencing behavioural intention to use m-Government services - Mohd Noor, Farhanah; Said, Mohd Fua'ad (Quantum Academic Publisher, 2021)
This study aimed to examine the role of behavioural intention to use m-Government services from Malaysian citizens perspectives. Drawing upon this aims, this study proposed personal innovativeness as a moderating variable in UTAUT2; performance expectancy, effort expectancy, social influence, facilitating condition and price value in predicting the behavioural intention to use the m-Government services. 354 data were collected through a self-administered questionnaire and was analysed using structural equation modelling to test the hypothesis. The findings found that performance expectancy, effort expectancy, social influence, facilitating condition and price value are the important determinant in influencing users‟ behavioural intention to use of m-Government services. Interestingly, this study found the significant moderating effect of personal innovativeness in a relationship of performance expectancy and effort expectancy on behavioural intention. This study has extended the understanding on the role of personal innovativeness towards users’ behavioural intention to use m-Government services.